Efficiency of Using Trichoderma, Mucor and Aspergillus Antimicrobial Pellets to Rhizophora mucronata Poir. Planting at Abandoned Shrimp Farm in Khanom District, Nakhon Si Thammarat Province, Thailand - Rattanaloeadnusorn, Sukhan (Naresuan University Journal: Science and Technology (NUJST), 2019)
Rhizophora mucronata Poir planting was non using antimicrobial pellets in spreading pathogens of genus Fusarium , Polyporus at abandoned shrimp farm area, Khanom District, Nakhon Si Thammarat Province, Thailand. The plants were short with 33% survival rate, low macronutrient, micronutrients and supplemented nutrients. Only 9 isolates of fungal biodiversity were found. When Trichoderma antimicrobial pellets were used to induce 2-3-folds of growth, 95 % of R . mucronata plants survived. This aimed to compare the height growth, survival rate, physical and biological properties before and after using the Trichoderma , Mucor and Aspergillus multi-antimicrobial pellets. However, using the Trichoderma , Mucor and Aspergillus multi-antimicrobial pellets for R . mucronata planting in spreading pathogens of Fusarium , Polyporus area, the highest growth was 4.30 folds and 99% of the plants survived. Furthermore, using these pellets in non pathogens, the growth was 4.02 folds and 99% of the plants survived, while the growth was 2.64 folds and 88% of the plants survived in the spreading area of these pellets. On the other hand, in the controlled area the growth was 0.42 folds and 88% of the plants survived. When the Trichoderma, Mucor and Aspergillus multi-antimicrobial secreted 1-aminocyclopropane-1-carboxylate (ACC) extraenzymes, ethylene synthesis decreased. When this ethylene in the plant reduced, the antimicrobial secreted. This induced IAA hormone to speed up the plants growth, dissolved phosphorus and fixed nitrogen. Macronutrients, micronutrients and supplemented nutrients increased in sediment soil between 45 to 2000%, while heavy metals reduced between 80 to 100%. The coefficients were more accurate than 95.5.  So government should develop R . mucronata or other mangrove plants in spread or non spread pathogens area by using Trichoderma, Mucor and Aspergillus multi-antimicrobial pellets in abandoned shrimp farm. Consequently, the area will be restored and returned to natural balance within 5 years.   Keywords: Trichoderma, multi-Antimicrobial Pellets , Rhizophora mucronata , Survival, Growth, Mangrove forest